Comparison of photoconductive semiconductor switch parameters with selected switch devices in power systems - Piwowarski, K. (Opto-Electronics Review, 2020)
Currently, work is underway to manufacture and find potential applications for a photoconductive semiconductor switch made of a semi-insulating material. The article analyzes the literature in terms of parameters and possibilities of using PCSS switches, as well as currently used switches in power and pulse power electronic system. The results of laboratory tests for the prototype model of the GaP-based switch were presented and compared with the PCSS switch parameters from the literature. The operating principle, parameters and application of IGBT transistor, thyristor, opto-thyristor, spark gap and power switch were presented and discussed. An analysis of the possibilities of replacing selected elements by the PCSS switch was carried out, taking into account the pros and cons of the compared devices. The possibility of using the currently made PCSS switch from gallium phosphide was also discussed.